Physiological and gene expression changes of Cryptomeria fortunei Hooibrenk families under heat stress - Xue, Jinyu; Zeng, Pingsheng; Cui, Jiebing; Zhang, Yingting; Yang, Junjie; Zhu, Lijuan; Hu, Hailiang; Xu, Jin (Frontiers in Plant Science, 2023)
Heat stress is one of the major abiotic stresses affecting plant growth and productivity. Cryptomeria fortunei (Chinese cedar) is an excellent timber and landscaping tree species in southern China because of its beautiful appearance, straight texture and ability to purify the air and improve the environment. In this study, we first screened 8 excellent C. fortunei families (#12, #21, #37, #38, #45, #46,, #48, #54) in a second generation seed orchard. We then analyzed the electrolyte leakage (EL) and lethal temperature at 50% (LT50) values under heat stress, to identify the families with the best heat resistance (#48) and the lowest heat resistance (#45) and determine the physiological and morphological response of different heat-resistant C. fortunei to heat stress. The relative conductivity of the C. fortunei families showed an increasing trend increasing temperature, following an "S" curve, and the half-lethal temperature was between 39 °C and 43.2 °C. The activities of SOD and POD fluctuated in the early stage of stress, but decreased after 37 °C. We observed the changes in the cell ultrastructure at 43 ℃, and the mesophyll cell structure of #48 was less damaged than that of #45. Eight heat resistance gene, including CfAPX1, CfAPX2, CfHSP11, CfHSP21, CfHSP70, CfHSFA1a, CfHSFB2a and CfHSFB4, were all upregulated in #45 and #48, and there were significant differences between #45 and #48 under different heat stress treatments. We found a significant difference in heat tolerance between #45 and #48, such that #48 has more heat tolerance capability and could be exploited in breeding programs. We conclude that the strongly heat-resistant family had a more stable physiological state and a wider range of heat stress adaptations